New Evidence on the Role of Catalase in Escherichia Coli-Mediated Biocorrosion - Paez-Collio, M; Paez-Collio, M; Zagal-Moya, J; Zagal-Moya, J; Vasquez-Guzman, C; Monsalve-Gonzalez, A; Melo-Hurtado, F; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Gulppi-Cabra, M; Gulppi-Cabra, M; Azocar-Guzman, M; et al. (2013)
The role of catalase on the microbiologically influenced corrosion mechanism by Escherichia coli (E. coli) has been examined, employing wild type and catalase-deficient cells. The bacteria were cultured for different times in the presence of AISI 316L stainless steel samples. The morphologies of the metallic surfaces covered by biofilms were studied by optical microscopy. The localized corrosion catalyzed by the bacteria was followed by scanning electron microscopy after immersion in the bacterial culture for different times. Susceptibility to corrosion was further investigated by potentiodynamic measurements. It was found that wild type E. coli is more aggressive than the mutant one, suggesting a role for catalase in increasing the kinetics of the cathodic reaction and, consequently, the global corrosion process. This correlates with oxygen uptake kinetics, as determined by differential pulse voltammetry on a pyrolytic graphite electrode modified with cobalt phthalocyanine, which was higher in the presence of wild type E. coli. When H2O2 was deliberately added to the culture medium, wild type E. coli catalyzed oxygen disproportionation more efficiently than the mutant derivative, thus limiting H2O2 accumulation in the medium and, hence, bacterial poisoning. In fact, the reduced adhesion of mutant cells to the metal substrate is apparently the result of H2O2 accumulation in the culture broth. Thus, the rapid consumption of oxygen and peroxide in the presence of wild type E. coli is associated with the catalysis of H2O2 disproportionation to water and oxygen. On the stainless steel, however, a dual mechanism of oxygen reduction, i.e. through formation of hydrogen peroxide and by formation of water, is also considered. © 2012 Elsevier Ltd.